2021
DOI: 10.1115/1.4050924
|View full text |Cite
|
Sign up to set email alerts
|

Friction Surfacing Deposition by Consumable Tools

Abstract: Friction surfacing is a new variation of friction stir processing for surface property modification of metallic substrates. There is an increasing body of literature about friction surfacing by deposition of metal from a consumable tool to a solid substrate. Friction surfacing has many potential applications in joining, coating for corrosion resistance, and repair of degraded components. This paper presents a review of the basic principles, the latest research, and process variations with emphasis on material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 152 publications
0
4
0
Order By: Relevance
“…The tool is displaced upwards by a predetermined level to deposit a subsequent layer leading to fabrication of 3D geometries. This technique is similar to friction surfacing in which a consumable feed rod is used instead of hollow tool which gets deposited as a layer [111,112]. There is a possibility of [37] composite fabrication through usage of hollow rods filled with ceramic powder as a feed-stock [113].…”
Section: Additive Friction Stir Depositionmentioning
confidence: 99%
“…The tool is displaced upwards by a predetermined level to deposit a subsequent layer leading to fabrication of 3D geometries. This technique is similar to friction surfacing in which a consumable feed rod is used instead of hollow tool which gets deposited as a layer [111,112]. There is a possibility of [37] composite fabrication through usage of hollow rods filled with ceramic powder as a feed-stock [113].…”
Section: Additive Friction Stir Depositionmentioning
confidence: 99%
“…1. Schematic diagram of friction surfacing process [3] Kumar et al [4] examined the effect of axial force, spindle speed and table speed on bonding strength and bend ductility for the deposition of AA6063 on the mild steel surface. The authors concluded that 1.25-1.3 mm deposition thickness provides maximum strength and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to FSW, additive friction stir deposition (AFSD) is a thermo-mechanical process derived from FSW, friction surfacing (FS) [13][14][15][16][17], and the friction stir forming technique [18]. The AFSD process utilizes frictional heat generated by a rotating tool and severe plastic deformation physics to plastically deform the material, inducing material flow to form a layer-by-layer AM process [19][20][21].…”
Section: Introductionmentioning
confidence: 99%